Formal methods and software engineering : 20th International Conference on Formal Engineering Methods, ICFEM 2018, Gold Coast, QLD, Australia, November 12-16, 2018, Proceedings /: 20th International Conference on Formal Engineering Methods, ICFEM 2018, Gold Coast, QLD, Australia, November 12-16, 2018, Proceedings. (2018) - Unknown
No abstract available